Analyzing Migratory Properties of Human CD133+ Stem Cells in Vivo after Intraoperative Sternal Bone Marrow Isolation. Issue 9 (September 2013) - Donndorf, Peter; Useini, Dritan; Lux, Cornelia A.; Vollmar, Brigitte; Delyagina, Evgenya; Laupheimer, Michael; Kaminski, Alexander; Steinhoff, Gustav
Human bone marrow stem cell populations have been applied for cardiac regeneration purposes within different clinical settings in the recent past. The migratory capacity of applied stem cell populations towards injured tissue, after undergoing specific peri-interventional harvesting and isolation procedures, represents a key factor limiting therapeutic efficacy. We therefore aimed at analyzing the migratory capacity of human cluster of differentiation (CD) 133 + bone marrow stem cells in vivo after intraoperative harvesting from the sternal bone marrow. Human CD133 + bone marrow stem cells were isolated from the sternal bone marrow of patients undergoing cardiac surgery at our institution. Migratory capacity towards stromal cell-derived factor-1α (SDF-1α) gradients was tested in vitro and in vivo by intravital fluoresecence microscopy, utilizing the cremaster muscle model in severe combined immunodeficient (SCID) mice and analyzing CD133 + cell interaction with the local endothelium. Furthermore, the role of a local inflammatory stimulus for CD133 + cell interaction with the endothelium was studied. In order to describe endothelial response upon chemokine stimulation laser scanning microscopy of histological cremaster muscle samples was performed. SDF-1α alone was capable to induce relevant early CD133 + cell interaction with the endothelium, indicated by the percentage of rolling CD133 + cells (45.9 ± 1.8% in "SDF-1" vs. 17.7 ± 2.7% in "control, " p < 0.001) and the significantly reduced rolling velocity after SDF-1α treatment. Furthermore, SDF-1α induced firm endothelial adhesion of CD133 + cells in vivo. Firm endothelial adhesion, however, was significantly enhanced by additional inflammatory stimulation with tumor necrosis factor-α (TNF-α) (27.9 ± 4.3 cells/mm 2 in "SDF-1 + TNF" vs. 2.2 ± 1.1 cells/mm 2 in "control, " p < 0.001). CD133 + bone marrow stem cells exhibit sufficient in vivo homing towards SDF-1α gradients in an inflammatory microenvironment after undergoing standardized intraoperative harvesting and isolation from the sternal bone marrow.